Ambulatory urodynamics in clinical practice: A single centre experience. Issue 8 (30th August 2019) - Cantu, Hector; Sharaf, Ala'a; Bevan, Wendy; Hassine, Anna; Hashim, Hashim
Abstract: Objectives: To assess the additional value of ambulatory urodynamics (AUDS) monitoring in the management of patients with unexplained lower urinary tract symptoms. Methods: A retrospective review of the urodynamic data at a tertiary referral center between January 2006 and December 2018. During this period 12, 123 urodynamic studies were conducted; 430 patients were arranged to have AUDS monitoring because their symptoms were not reproduced with either standard or video urodynamics (UDS). Results: A total of 391 patients were included, (360 females, 31 males). Symptoms were reproduced in 74% of cases. The most common AUDS finding was detrusor overactivity with or without incontinence, followed by urodynamic stress incontinence. In 75.7% of the patients, the additional information from AUDS resulted in a change to patient management. Conclusions: Additional UDS findings were made in the majority of patients who underwent AUDS. This helped in setting a new treatment plan for the bothersome urinary findings. AUDS monitoring is a useful additional diagnostic tool and can help to guide patient management where symptoms are not explained by standard or video UDS.